2 TSPO PET imaging of inflammation with [18F]LW223 predicts functional outcome following myocardial infarction. (22nd March 2023) - MacAskill, Jen; Reid, Victoria; Alcaide-Corral, Carlos; Morgan, Timaeus; De Albuquerque, Ana Clara Juan; Thomson, Adrian; Fujisawa, Takeshi; Mills, Nicholas; Knyzeliene, Agne; Balogh, Viktoria; Wimberley, Catriona; Dweck, Marc; et al.
Abstract : Inflammation is a key process influencing left ventricular remodelling following myocardial infarction (MI) and can be imaged using Positron Emission Tomography (PET) targeting the 18Da translocator protein (TSPO). We have developed the TSPO radiotracer [ 18 F]LW223, that overcomes several barriers holding back wide adoption of TSPO imaging. This study utilised a rat MI-model to assess whether [ 18 F]LW223 could accurately detect inflammation, and if this was predictive of cardiac function. Male Sprague-Dawley rats underwent coronary artery ligation (30 min), followed by reperfusion to induce MI. [ 18 F]LW223 PET was performed on d2, 7, 14 and 28. On d28, cardiac function was assessed by ultrasound. Naïve (n=10) and sham (n=6) rats were used as controls for comparison to the MI (n=5). A separate cohort of naïve (n=8), sham (n=18) and MI (n=17) rats were produced for histological validation. Troponin I measurements suggested a range of infarct severities (2583-10970ng/L). [ 18 F]LW223 signal was highest within the MI cohort, and localised to the infarct. [ 18 F]LW223 binding peaked at d2, with a smaller secondary peak within the infarct at d28. Manual counting by histology validated this pattern, and revealed that the majority of TSPO expressing cells within the infarct also expressed the monocyte/macrophage marker CD68 (55.2%). Finally, infarct [ 18 F]LW223 signal at d2 correlated with infarct severity, and systolic dysfunction at d28. [ 18 F]LW223 was able to map macrophage-driven inflammation in this model, with expression peaking on day 2, the extent of which was predictive of reduced cardiac function at day 28.